A violência do preconceito: a desagregação dos vínculos coletivos e das subjetividades - Angela Maria Pires Caniato (Arquivos Brasileiros de Psicologia, 2014)
Prejudice is one of the most perverse oppression strategies that governs the discriminatory process among peoples. Violence in bias is frequently camouflaged under the guise of a “democratic” society, made up of “civilized” people, that offers “security” to all. These terms are spread through ideological representations that act over individuals very much in the manner as the Cultural Industry, or rather, they are somewhat internalized in a unconscious mode. Individuals are thus thrown into a psychic regression by which they lose their ability to think critically and act according to a protecting stance. In other words, they lose their capacity to defend themselves against social hostility. Besides isolating individuals, the violence of prejudice introduces distrust among colleagues and functions within the context of a severe self-punishment of blame complex. Individuals affected by bias become accomplices of the social process that deceives and violates them.